Techno-Economic Analysis of MPPT and PWM Controllers Performance in Off-Grid PV Systems - Robles-Algarín, Carlos; Olivero-Ortíz, Víctor; Restrepo-Leal, Diego (International Journal of Energy Economics and Policy, 2022)
The type of controller implemented in a photovoltaic system is of vital importance, since these devices control the energy input coming from the solar modules to regulate the batteries charge. An efficient controller makes it possible to take full advantage of the solar modules power, maximizing the energy obtained. In this paper a techno-economic analysis to measure the performance of MPPT and PWM controllers in a low power off-grid PV system is presented. To achieve this objective, the modeling of a 65 W PV system was performed, which is composed of a solar module, a DC-DC converter, a controller, and a 12 V battery. The modeling was performed in Matlab-Simulink, with which the power data and average monthly energy generated were obtained, using the city of Santa Marta Colombia as a case study. The technical results show that the MPPT controller generates a higher amount of monthly average energy (10.5 kWh) compared to the PWM controller (7.19 kWh) and the data estimated in the Global Solar Atlas (8.22 kWh). From the economic perspective, it was shown that it is possible to implement MPPT controllers in low-power PV systems, due to the energy surpluses obtained and the investment recovery time.